The Transformation of Spiritual Culture in the Context of the Formation of the "New Ethics" (Problem Statement) - Chukurov, Andrey (Slavica, 2021)
The article is devoted to the analysis of the spiritual values that are being formed today and the reasons for the actualization of the New Ethics. Catastrophic dynamism leads to the elimination of the stable social groups as well as to the maximum diffuseness of personal boundaries. At the same time, the transformation of the communication system brings an extremely vulnerable virtual body to the forefront of cultural life. The new communication system, social atomization, the lack of understandable guidelines in the process of socialization and self-identification - all this turns the concept of “border” into a basic one for the New Ethics. However, the design of boundaries and self-defense mechanisms does not always lead to the expected positive results. We come to the conclusion, that an initially inadequate assessment of the aggressiveness of the environment forces a person to build the most aggressive defense mechanisms: the man himself is transformed into a source of toxicity, which in turn makes the environment even more toxic than it was originally.